Simulation of targets and backgrounds in sonar/radar systems - Lew, Henry. (2008)
Echolocation systems such as sonar and radar provide an important means of detecting, classifying, and tracking targets that are well beyond the range of human perception. However, the problem of achieving robust performance in a variety of situations is a difficult one. This is due to the limitations placed on sensor performance by the operating environment and the target itself. Therefore, it is essential to understand the characteristics of the target and the environment, as well as the mechanisms responsible for them, from the viewpoint of the sensor. To this end, this project has initiated the modelling and simulation of targets and backgrounds, especially in terms of the echo time series. Because this is only a one year project, the scope has been limited to that of high frequency acoustic scattering pertaining to active sonar systems. However, the techniques can be applied equally well to electromagnetic systems that do not consider polarization.